Contents and Foreword of the ATIKAN Journal, issue of June 2014 - ATIKAN, Editor Journal (ATIKAN, 2014)
This journal, with ISSN 2088-1290, was firstly published on June 1, 2011. Since issue of June 2012, the ATIKAN journal has been organized by the Lecturers of FKIP UNSUR (Faculty of Education and Teacher Training, Suryakancana University) in Cianjur, West Java, Indonesia; and published by Minda Masagi Press as one of the publishers owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung. The ATIKAN journal is published twice a year i.e. every June and December.Â